Translation and cross-cultural adaptation of the Get Active Questionnaire for Pregnancy (GAQ-P) to Spanish population - Eva Ferrer; Maia Brik; Margie Davenport; Ruben Barakat; Montse Palacio (Apunts Sports Medicine)
Background: Physical activity during pregnancy reduces the risk of developing pregnancy complications. Despite the strong recommendations for physical activity during pregnancy, the compliance is suboptimal. The Get Active Questionnaire for Pregnancy (GAQ-P), developed by CESP provides a screening tool for physical activity contraindications and promotes physical activity during pregnancy. The aim of this study is to translate, and perform a cross-cultural adaptation of the GAQ-P to be used in Spanish population. Methods: A multidisciplinary expert group was set-up for the validation process including experts in obstetrics and gynecology, sports medicine, physical activity and sports, and midwives. The translation and cultural adaptation of the GAQ-P and associated Health Care Provider Consultation Form followed the International Society for Pharmaecoeconomics and Outcomes Research guidelines. Results: The validated Spanish version of the GAQ-P, and the Health Care Provider Consultation Form for Prenatal Physical Activity was achieved. During the cognitive debriefing, we included 73 stakeholders (pregnant women, healthcare professionals and physical activity and sports professionals) from different regions of Spain, to improve the cultural aspects and the comprehensibility of the translation. Conclusions: Following the validation process, we have obtained a reliable evidence-based screening tool to be used in Spanish, aiming to reduce the barriers for most women to be physically active during pregnancy, and assisting healthcare providers and physical activity professionals in the identification of women that have contraindications for physical activity during pregnancy.